The General And Theoretical Foundations Of Literacy Teaching In Primary School Students (Eurasian Journal of Learning and Academic Teaching, 2025)
This article explores the theoretical foundations and practical approaches of literacy teaching methodologies for primary school students. It highlights the techniques and tools employed in the development of reading and writing skills. The study analyzes the process of systematically improving students’ reading and writing competencies through the analytical-synthetic phonics method, emphasizing the interrelation between phonetic and graphic units. Furthermore, the importance of methodological approaches in establishing solid literacy foundations among young learners is examined